Evaluation of natural radionuclides for mica and quartz in Eastern Desert of Egypt, using gamma-ray spectrometry - N. Walley El-Dine; A. El-Shershaby; S. Afifi; S. El-Bahi; E. Samir (Ядерна фізика та енергетика)
By applying high–resolution γ-ray spectroscopic system, the various radionuclides of mica and quartz samples have been identified quantitatively. The specific activity of 226Ra, 232Th and 40K in 25 mica samples collected from 5 locations and 15 quartz samples from 3 locations of geographical areas located in G. Kadabora in Central Eastern Desert of Egypt, were determined by gamma ray spectrometry with a high-purity germanium (HPGe) detector. This subject is important in environmental radiological protection, since mica and quartz are widely used as raw materials in different industries. The results of analysis for 238U, 232Th and 40K specific activities were found to be higher than the permissible level for all mica and quartz samples. The radium equivalent activities in Bq/kg, dose rate in nGy/hr, external and internal hazards in nGy/yr and also (232Th/238U) ratios Clark’s value s are calculated. From this study, it is clear that G. Kadabora, Central Eastern Desert, Egypt can be considered unsafe to use as raw materials.